Mission-oriented innovation policy in Norway Challenges, opportunities and future options - Larrue, Philippe (OECD Science, Technology and Industry Policy Papers, 2021)
This report assesses the potential for mission-oriented innovation policies (MOIPs) to contribute to the sustainable transition in Norway, and examines the challenges and opportunities that MOIPs would present. As part of a series of MOIP national case studies, the report finds that MOIPs could contribute significantly to alleviating some of the long-standing limitations of Norway's innovation system, acknowledging the country's strong advantages for mission-orientation and its innovative policy experimentations, such as the Pilot-E scheme and the CLIMIT programme. It proposes two options for Norway's future MOIP approach, with corresponding recommendations. Under a 'scaling-up' option, Norway would develop a system to manage the implementation of cross-agency schemes in relevant challenge areas. A 'levelling-up' option would involve the programming of a pilot mission in the four-year investment plan of the next edition of Norway's Long Term Plan, with support from high-level policy and political actors